Daycare enrollment age and child development - Mette Gørtz; Vibeke Myrup Jensen; Sarah Sander (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
A large share of young mothers return to work before their child turns one year. Exploiting exogenous variation in daycare vacancy rates, we estimate the causal effects of enrollment age in universal daycare on child development for children younger than two years. We find modest effects of postponing daycare enrollment on early childhood outcomes. Children who enroll later have fewer visits to their primary care physician in their first years of daycare, but the effects vanish before preschool. Children who enroll later are also more likely to have insufficient language proficiency at age five and thus need additional language support.
Keywords: I00; J13; J24; 330; Daycare; child development; health; cognitive skills